PROTECTION OF DRAWINGS AND PATTERNS IN INTERNATIONAL LAW - OVIDIA JANINA IONESCU (Challenges of the Knowledge Society)
Intellectual property occupies a fundamental place in the legal field, namely it represents the creation, development and evolution of society, with implications in all areas of activity. In recent time, highly advanced technology and the evolution of society in all fields, including in terms of designs, needs expeditious protection, considering also the amazing development recorded in this regard. In order to be protected, designs (and others) should benefit from such protection not only in the country of origin; namely, protection must be ensured internationally, otherwise it would not have the desired effect and the aim sought, meaning that the rightful authors would no longer enjoy all the rights they have over their creation. This paper aims to specify the applicable international intellectual property laws, namely on protection of designs, the main objective of these legal regulations, and some detailing considered emblematic to be mentioned, our country's accession to these international bodies, as appropriate, or their applicability into the national legal framework. Thus, the goal consists in identifying and detailing the protection that the designs enjoy at international level, respectively the international legislation implementation in the domestic legal framework, and our accession to the international organizations, or amending domestic legislation so as to correlate with the international laws, that is to protect intellectual property through this procedure, including the significance of these international regulations on protection of designs, both nationally and internationally.